Komunikasi Kelompok Sadar Pariwisata Dalam Pembangunan Berkelanjutan - Zis, Sirajul Fuad; Yonariza, Yonariza; Tanjung, Hery Bachrizal; Arief, Ernita (JURNAL TERAPAN PEMERINTAHAN MINANGKABAU, 2024)
The LPPL Tourism Awareness Group is a group that manages Ecotourism based on Disaster Risk Reduction. This research examines the dynamics of group communication in Sustainable Development in Nagari Ampian Parak, Pesisir Selatan Regency. This research uses qualitative research methods with in-depth interview techniques and observation. The results of this study found that group communication that occurs in the LPPL Tourism Awareness Group is led by the group leader openly with group members so that group members believe and want to work together to manage Ecotourism sustainably. The group leader has the power of communication to influence members to want to work together to plant sea pine and mangrove vegetation in cooperation. The study of Group Communication needs to be explored as an increase in the science of communication studies that develops according to the conditions of the times.